Rafael Ballester and his history of Spain text book: an example of the didactic renewal of the beginning of the 20th century - Valls, Rafael (Historia y Memoria de la Educación, 2018)
Without doubt, the most outstanding professional and intellectual contribution, among the different activities carried out by Rafael Ballester in the first three decades in the 20th century, was that of authoringnumerous remarkably successful school textbooks.. The figure of this high school teacher personifies the worries, determinations and efforts of the Institución Libre de Enseñanza to improve history and geography teaching in Spain. His other facets, as a historian of education, as a researcher of scientific methodology and didactics of teaching and as a pioneer in studies of historic historiography, pale beside the strength of his contributions as a successful author of school handbooks of history and geography.